Ketebalan Daun dan Laju Transpirasi Tanaman Hias Monokotil - Chindy Sulastri Ningsih; Entin Daningsih (Jurnal Ilmu Pertanian Indonesia, 2022)
Leaves are the main organ in plants. In general, leaf thickness varies amongst plants and is related to the transpiration rate. This study measured leaf thickness and transpiration rate in six ornamental monocotyledon plants. The experiment used Factorial Completely Randomized Design (CRD) with three replications. The main factors were six monocotyledon plants and three plant parts; combination factors were interactions between plant species and plant parts. Leaf thickness was measured from the upper to the lower epidermis before and after measuring the transpiration rate. The transpiration rate was measured by weighing. The data were analyzed using SAS with the Factorial CRD model and continued with LSD if the treatment was significant. The plant types and parts significantly affected the leaf thickness and transpiration rate. However, the combination treatments between plant types and plant parts significantly affected only the transpiration rate. Chlorophytum comosum L. had the highest transpiration, followed by Dracaena reflexa, Aglonema crispum, Cordyline fruticosa, Crymum asiaticum, and Rhoeo discolor. The leaves of the lower parts of the plant had the highest transpiration rate compared to the middle and upper parts of the plant. Rhoeo discolor had the thickest leaves and lower transpiration rate than other plants. The leaf thickness ranged from 95.94 µm to 147.03 µm. This phenomenon indicated that the thickness of the leaves was inversely correlated to the transpiration rate. Keywords: leaf thickness, transpiration rate, monocotyledon, ornamental plant